Extracellular membrane vesicles from Limosilactobacillus reuteri strengthen the intestinal epithelial integrity, modulate cytokine responses and antagonize activation of TRPV1 - Pang, Yanhong; Ermann Lundberg, Ludwig; Mata Forsberg, Manuel; Ahl, David; Bysell, Helena; Pallin, Anton; Sverremark-Ekström, Eva; Karlsson, Roger; Jonsson, Hans; Roos, Stefan (Frontiers in Microbiology, 2022)
Bacterial extracellular membrane vesicles (MV) are potent mediators of microbe-host signals, and they are not only important in host-pathogen interactions but also for the interactions between mutualistic bacteria and their hosts. Studies of MV derived from probiotics could enhance the understanding of these universal signal entities, and here we have studied MV derived from Limosilactobacillus reuteri DSM 17938 and BG-R46. The production of MV increased with cultivation time and after oxygen stress. Mass spectrometry-based proteomics analyses revealed that the MV carried a large number of bacterial cell surface proteins, several predicted to be involved in host-bacteria interactions. A 5’-nucleotidase, which catalyze the conversion of AMP into the signal molecule adenosine, was one of these and analysis of enzymatic activity showed that L. reuteri BG-R46 derived MV exhibited the highest activity. We also detected the TLR2 activator lipoteichoic acid on the MV. In models for host interactions, we first observed that L. reuteri MV were internalized by Caco-2/HT29-MTX epithelial cells, and in a dose dependent manner decreased the leakage caused by enterotoxigenic E. coli by up to 65%. Furthermore, the MV upregulated IL-1β and IL-6 from peripheral blood mononuclear cells (PBMC), but also dampened IFN-γ and TNF- responses in PBMC challenged with Staphylococcus aureus. Finally, we showed that MV from the L. reuteri strains have an antagonistic effect on the pain receptor TRPV1 in a model with primary dorsal root ganglion cells from rats. In summary, we have shown that these mobile nanometer scale MV reproduce several biological effects of L. reuteri cells and that the production parameters and selection of strain have an impact on the activity of the MV. This could potentially provide key information for development of innovative and more efficient probiotic products.